High electromagnetic shielding nanofiber aerogel with gradient structure and preparation method thereof
By using a gradient structure of high electromagnetic shielding nanofiber aerogel in electromagnetic shielding materials, the bonded interwoven structure of PVA-co-PE nanofibers, graphene oxide and silver nanowires are used to form a multi-layer structure, and the existing structure is solved. The problem of narrow wave absorption frequency and poor performance of electromagnetic shielding materials achieves efficient electromagnetic shielding effect in a wide frequency range.
Patent Information
- Application Number
- CN202211520420.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-11-30
AI Technical Summary
The existing electromagnetic shielding materials are narrow in the absorbing frequency, and are unable to achieve efficient electromagnetic shielding at wide frequencies, and conventional methods lead to electromagnetic wave reflection and secondary pollution.
High electromagnetic shielded nanofiber aerogel with gradient structure is used to form aerogel sheets of different pore sizes through the bonding interwoven structure of PVA-co-PE nanofibers, graphene oxide and silver nanowires, and is lyophilized and molded. Adhesive technology, forming a multi-layer structure to improve electromagnetic shielding performance.
It achieves excellent electromagnetic shielding performance in a wide frequency range, solves the problems of narrow wave absorbing frequency and poor electromagnetic shielding performance, and improves the electromagnetic shielding efficiency and material stability.
Smart Images

Figure CN115782339B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding materials, and in particular to a high electromagnetic shielding nanofiber aerogel with a gradient structure and a preparation method thereof. Background Art
[0002] With the rapid development of the electronic communications industry, a large number of emerging electronic devices have poured into various fields of life such as transportation, communications, and household appliances, providing great convenience for human life. However, electronic devices also generate electromagnetic interference and electromagnetic radiation of different frequencies, which not only affects the performance and service life of the device itself and surrounding equipment, but also causes certain harm to people's health. For example, with the increase of communication frequency, the communication base station is compressed into the size of a suitcase, which not only increases the interference between electromagnetic signals, but also requires the addition of new antennas at the signal receiving end of the communication equipment, further reducing the design space of the receiving end, and further enhancing the interference of electromagnetic signals. Therefore, electromagnetic shielding materials have become a research hotspot.
[0003] At present, the preparation method of electromagnetic shielding materials is usually to compound conductive fillers with polymer matrix to give polymer high conductivity and thus improve electromagnetic shielding performance. Commonly used conductive fillers are metals, metal nanowires, graphene, etc. Although this achieves a high shielding value to a certain extent, most electromagnetic waves are reflected on the surface of the material, causing secondary pollution.
[0004] Nanofiber-based aerogel products have excellent properties such as large specific surface area, high porosity, tortuous pore structure and high filtration accuracy, and have great potential in various application fields. The patent with application number CN201811461005.9 discloses a graphene aerogel with controllable elasticity for electromagnetic shielding and its preparation method. It directly uses graphene oxide and silver nanowire dispersion to prepare graphene / silver nanowire aerogel with uniform structure and controllable elasticity by a simple atmospheric pressure drying method. Although this method is simpler and has lower energy consumption than conventional methods, its electromagnetic shielding performance still needs to be improved; furthermore, the aerogel prepared by this method has a narrow absorption frequency of electromagnetic waves and cannot achieve broadband absorption.
[0005] In view of this, it is necessary to design an improved gradient structure high electromagnetic shielding nanofiber aerogel and a preparation method thereof to solve the above problems. Summary of the invention
[0006] The invention aims to provide a nanofiber aerogel with high electromagnetic shielding and a preparation method thereof with a gradient structure. PVA-co-PE nanofiber is used as a substrate, and graphene oxide and silver nanowire are used as wave absorbing media. First, a PVA-co-PE nanofiber suspension is prepared, and then graphene oxide and silver nanowire are added thereto. The silver nanowire, graphene oxide and PVA-co-PE nanofiber are bonded and interwoven to form a special bonded interwoven structure. Then, through freeze-drying treatment, as water and isopropanol are continuously evaporated, PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes and uniform pores are formed. Finally, the PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are bonded in order from small to large pore sizes to obtain a nanofiber aerogel with high electromagnetic shielding and a gradient structure. By utilizing the synergistic effect of silver nanowires, graphene oxide and PVA-co-PE nanofibers as well as the synergistic effect between different layers, when magnetic waves pass through the high electromagnetic shielding nanofiber aerogel, the electromagnetic waves are continuously reflected and absorbed in the pores of the high electromagnetic shielding nanofiber aerogel with a gradient structure, resulting in excellent electromagnetic shielding performance.
[0007] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure, comprising the following steps:
[0008] S1. Mix isopropanol, deionized water and PVA-co-PE nanofibers in a certain proportion to prepare a PVA-co-PE nanofiber suspension of a preset concentration;
[0009] S2. adding graphene oxide and silver nanowires in a preset ratio to the PVA-co-PE nanofiber suspension prepared in step S1, and freeze-drying to prepare PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes;
[0010] S3. Several PVA-co-PE / AgNW / GO aerogel sheets prepared in step S2 are bonded in order from small to large pore sizes to obtain a high electromagnetic shielding nanofiber aerogel with a gradient structure.
[0011] As a further improvement of the present invention, in step S2, the mass ratio of the PVA-co-PE nanofibers, graphene oxide and silver nanowires is 9.5:0.25:0.25-1:4.5:4.5.
[0012] As a further improvement of the present invention, in step S1, the mass ratio of isopropanol, deionized water and PVA-co-PE nanofibers is 49.5:49.5:1-47.5:47.5:5; and the concentration of the obtained PVA-co-PE nanofiber suspension is 1-5wt%.
[0013] As a further improvement of the present invention, the diameter of the PVA-co-PE nanofiber is 100-300 nm.
[0014] As a further improvement of the present invention, the pore size of the high electromagnetic shielding nanofiber aerogel with a gradient structure is 1-100 μm, and the pore size difference between adjacent PVA-co-PE / AgNW / GO aerogel sheets is 10-90 μm.
[0015] As a further improvement of the present invention, the high electromagnetic shielding nanofiber aerogel with a gradient structure is composed of at least two layers of PVA-co-PE / AgNW / GO aerogel sheets, and the total thickness is no more than 9 mm.
[0016] As a further improvement of the present invention, in step S2, freeze drying is specifically as follows: adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and adding the suspension to a culture dish, freezing at (-70)-(-90)°C for 20-30h, and then drying at (-40)-(-70)°C for 10-80h;
[0017] The freeze-drying treatments of PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes were different.
[0018] As a further improvement of the present invention, in step S3, PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are molded and bonded using polydimethylsiloxane.
[0019] To achieve the above-mentioned purpose of the invention, the present invention also provides a high electromagnetic shielding nanofiber aerogel with a gradient structure, which is prepared by the above-mentioned preparation method of the high electromagnetic shielding nanofiber aerogel with a gradient structure.
[0020] As a further improvement of the present invention, the electrical conductivity of the high electromagnetic shielding nanofiber aerogel is as high as 5800s / cm, the electromagnetic shielding effectiveness is as high as 56.8dB, and the wave absorption frequency band is 8-13GHz.
[0021] The beneficial effects of the present invention are:
[0022] (1) The preparation method of the high electromagnetic shielding nanofiber aerogel with a gradient structure provided by the present invention comprises the following steps: using PVA-co-PE nanofiber as a substrate, graphene oxide and silver nanowires as wave absorbing media, firstly preparing a PVA-co-PE nanofiber suspension, and then adding graphene oxide and silver nanowires therein, wherein the PVA-co-PE nanofiber has a special porosity and linear structure, and its surface contains abundant active groups; graphene oxide has a certain hydrophilicity, and has excellent dispersibility in the PVA-co-PE nanofiber suspension, and its surface contains a large number of oxygen-containing functional groups, which are active in nature and can easily react with silver nanowires, PVA-co-PE nanofibers, and graphene oxide. VA-co-PE nanofibers are bonded together by chemical bonds; at the same time, silver nanowires have high electrical conductivity and a large aspect ratio, so that silver nanowires, graphene oxide and PVA-co-PE nanofibers are bonded and interwoven to form a special bonded interwoven structure; then, through freeze-drying treatment, as water and isopropanol continue to evaporate, PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes and uniform pores are formed. The resulting sheets not only combine the strength of the interwoven structure, but also the graphene oxide and silver nanowires are evenly distributed, thus forming a conductive path, and the conductive properties are the same everywhere, so that it has efficient electromagnetic shielding performance. Finally, PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are bonded in order from small to large pore sizes to obtain a high electromagnetic shielding nanofiber aerogel with a gradient structure. Through molded bonding, adjacent layers are further interwoven, and the synergistic effect of silver nanowires, graphene oxide and PVA-co-PE nanofibers and the synergistic effect between different layers are utilized. When magnetic waves pass through the high electromagnetic shielding nanofiber aerogel, the electromagnetic waves are continuously reflected and absorbed in the pores of the high electromagnetic shielding nanofiber aerogel with a gradient structure, resulting in excellent electromagnetic shielding performance.
[0023] (2) The high electromagnetic shielding nanofiber aerogel with a gradient structure provided by the present invention has excellent electromagnetic shielding performance in a wide frequency range due to the synergistic effect between the various raw materials and the gradient structure, which solves the problem of the narrow wave absorption frequency of the current electromagnetic shielding materials; at the same time, the electromagnetic shielding superposition effect is achieved in the wide frequency band, the electromagnetic shielding performance is improved, and the bottleneck problem of poor electromagnetic shielding performance of conventional materials is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a process flow chart of the preparation method of the high electromagnetic shielding nanofiber aerogel with a gradient structure.
[0025] Figure 2 This is a schematic diagram of the three-dimensional structure of the high electromagnetic shielding nanofiber aerogel prepared in Example 1 of the present invention.
[0026] Figure 3This is a scanning electron microscope image of the high electromagnetic shielding nanofiber aerogel prepared in Example 1, with a scale of 50 μm.
[0027] Figure 4 This is the stress-strain diagram of 30 cycles of compression of the high electromagnetic shielding nanofiber aerogel prepared in Example 1.
[0028] Figure 5 This is a curve chart of electromagnetic shielding data of the high electromagnetic shielding nanofiber aerogel prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0032] See also Figure 1 As shown, the present invention provides a method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure, comprising the following steps:
[0033] S1. Disperse and mix isopropanol, deionized water and PVA-co-PE nanofibers in a mass ratio of 49.5:49.5:1-47.5:47.5:5 in a high-speed shearing machine to prepare a PVA-co-PE nanofiber suspension with a concentration of 1-5wt%.
[0034] The diameter of PVA-co-PE nanofibers is 100-300nm. In this process, PVA-co-PE nanofibers are cut into different fragments and evenly dispersed in isopropanol and deionized water.
[0035] S2. Adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and freeze-drying to prepare PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes.
[0036] Among them, the mass ratio of PVA-co-PE nanofibers, graphene oxide and silver nanowires is 9.5:0.25:0.25-1:4.5:4.5.
[0037] Freeze drying is specifically as follows: adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and adding the suspension to a culture dish, freezing it at (-70)-(-90)°C for 20-30 hours, preferably freezing it at -80°C for 24 hours, and then drying it at (-40)-(-70)°C for 10-80 hours, preferably drying it at -55°C.
[0038] The freeze-drying treatments of PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes were different.
[0039] In this process, graphene oxide and silver nanowires are firstly evenly dispersed in the PVA-co-PE nanofiber suspension. Graphene oxide has a certain hydrophilicity and has excellent dispersibility in the PVA-co-PE nanofiber suspension. At the same time, its surface contains a large number of oxygen-containing functional groups, which are active in nature and can easily bond with silver nanowires and PVA-co-PE nanofibers through chemical bonds to form a special bonding structure. In addition, silver nanowires have high electrical conductivity, and their large aspect ratio is more conducive to the interweaving of silver nanowires, graphene oxide and PVA-co-PE nanofibers, further forming a special bonding interweaving structure, and forming a conductive path at the same time; it also avoids the corrosion of silver nanowires and improves the service life. Then, through freeze-drying treatment, as water and isopropanol continue to evaporate, a PVA-co-PE / AgNW / GO aerogel sheet with uniform pores is formed.
[0040] Due to the different proportions of raw materials and specific freeze-drying treatments in PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes, firstly, the bonded interwoven structures of silver nanowires, graphene oxide and PVA-co-PE nanofibers are different, and secondly, the evaporation rates and evaporation amounts of water and isopropanol are different, resulting in differences in the microstructure and pore size of PVA-co-PE / AgNW / GO aerogel sheets.
[0041] S3. Several PVA-co-PE / AgNW / GO aerogel sheets prepared in step S2 are bonded in order from small to large pore sizes, and different PVA-co-PE / AgNW / GO aerogel sheets are molded and bonded using polydimethylsiloxane to obtain a high electromagnetic shielding nanofiber aerogel with a gradient structure.
[0042] Specifically, the gradient structured high electromagnetic shielding nanofiber aerogel is composed of at least two layers of PVA-co-PE / AgNW / GO aerogel sheets with a total thickness not exceeding 9 mm.
[0043] The pore size of the gradient-structured high electromagnetic shielding nanofiber aerogel is 1-100 μm, and the pore size difference between adjacent PVA-co-PE / AgNW / GO aerogel sheets is 10-90 μm.
[0044] The present invention also provides a high electromagnetic shielding nanofiber aerogel with a gradient structure, which is prepared by the above-mentioned preparation method of the high electromagnetic shielding nanofiber aerogel with a gradient structure. The high electromagnetic shielding nanofiber aerogel has an electrical conductivity of up to 5800s / cm, an electromagnetic shielding effectiveness of up to 56.8dB, and an absorption frequency band of 8-13GHz.
[0045] The present invention is described in detail below through a number of embodiments:
[0046] Example 1
[0047] A method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure comprises the following steps:
[0048] S1. Disperse and mix isopropanol, deionized water and PVA-co-PE nanofibers in a mass ratio of 48.5:48.5:3 in a high-speed shearing machine to prepare a PVA-co-PE nanofiber suspension with a concentration of 3 wt%.
[0049] The diameter of PVA-co-PE nanofibers is 180 nm.
[0050] S2. Adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and freeze-drying to prepare PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes.
[0051] The proportions of raw materials and freeze-drying treatments in PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are different. Specifically: Sheet 1, PVA-co-PE / AgNW / GO raw material ratio is 6:2:2, drying time is 12h, air flow rate is 20μL / min, and pore size is 10μm; Sheet 2, PVA-co-PE / AgNW / GO raw material ratio is 4:3:3, drying time is 24h, air flow rate is 20μL / min, pore size is 30μm; Sheet 3, PVA-co-PE / AgNW / GO raw material ratio is 2:4:4, drying time is 72h, air flow rate is 20μL / min, pore size is 90μm. (The pore size can also be adjusted by changing the air flow rate)
[0052] S3. Three PVA-co-PE / AgNW / GO aerogel sheets prepared in step S2 are bonded in order from small to large pore sizes, and different PVA-co-PE / AgNW / GO aerogel sheets are molded and bonded using polydimethylsiloxane (such as Figure 2 As shown), a high electromagnetic shielding nanofiber aerogel with a gradient structure is obtained. The total thickness is 9 mm.
[0053] like Figure 3 As shown, the pore size of the obtained high electromagnetic shielding nanofiber aerogel gradually increases, the pores of each layer are relatively uniform, and the interwoven bonding structure can be seen.
[0054] like Figure 4 As shown, the compressive stress-strain properties of the obtained high electromagnetic shielding nanofiber aerogel basically tend to be stable when subjected to 30 cycles of compression, indicating that the obtained high electromagnetic shielding nanofiber aerogel has good stability and high reusability.
[0055] like Figure 5 As shown, the electromagnetic shielding effectiveness of the obtained high electromagnetic shielding nanofiber aerogel is 56.8dB, the wave absorption frequency band is between 8-13GHz, the electromagnetic shielding performance is excellent, and the wave absorption frequency band is wide.
[0056] Examples 2-3 and Comparative Example 1
[0057] A method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure, compared with Example 1, is different in that, in step S1, the concentration of the PVA-co-PE nanofiber suspension is different, and the rest is substantially the same as Example 1 and will not be repeated here.
[0058] The performance of the high electromagnetic shielding nanofiber aerogels with gradient structures prepared in Examples 1-3 and Comparative Example 1 was tested, and the results are shown in Table 1:
[0059] Table 1 Performance of high electromagnetic shielding nanofiber aerogels prepared in Examples 1-3 and Comparative Example 1
[0060]
[0061] It can be seen from Table 1 that with the increase of the concentration of the PVA-co-PE nanofiber suspension, the electromagnetic shielding performance and mechanical properties of the obtained high electromagnetic shielding nanofiber aerogel both show a trend of first increasing and then decreasing. The concentration of the PVA-co-PE nanofiber suspension has a great influence on the conductivity, electromagnetic shielding performance and compressive stress of the material. A low concentration is not conducive to the formation of the porous structure, resulting in poor electromagnetic shielding performance and mechanical properties; a high concentration reduces the conductivity of the material, the electromagnetic shielding performance, and the mechanical properties. Example 1 is the optimal nanofiber concentration value.
[0062] Examples 4-5 and Comparative Example 2
[0063] A method for preparing a nanofiber aerogel with a gradient structure and high electromagnetic shielding, compared with Example 1, the difference is that in step S2, the mass ratio and pore size of PVA-co-PE nanofibers, graphene oxide and silver nanowires are different, and the rest is roughly the same as Example 1, which will not be repeated here. The specific ratio and pore size of the raw materials in each layer of PVA-co-PE / AgNW / GO aerogel sheet are shown in Table 2.
[0064] Table 2 Parameters of PVA-co-PE / AgNW / GO aerogel sheets in Examples 4-5 and Comparative Example 2
[0065]
[0066] The performance of the high electromagnetic shielding nanofiber aerogels with gradient structures prepared in Examples 4-5 and Comparative Example 2 was tested, and the results are shown in Table 3:
[0067] Table 3 Performance of high electromagnetic shielding nanofiber aerogels prepared in Examples 4-5 and Comparative Example 2
[0068]
[0069] It can be seen from Table 3 that when the content of PVA-co-PE nanofibers increases, the content of graphene oxide and silver nanowires decreases, resulting in a decrease in conductivity and electromagnetic shielding performance. When the mass ratio of PVA-co-PE nanofibers, graphene oxide and silver nanowires remains unchanged, the larger the pore size, the lower the conductivity and electromagnetic shielding performance, and the narrower the effective absorbing frequency band width.
[0070] When the mass ratio of graphene oxide and silver nanowires is not 1:1, the performance of the obtained high electromagnetic shielding nanofiber aerogel decreases. This may be due to the poor bonding structure formed by silver nanowires, graphene oxide and PVA-co-PE nanofibers at this time.
[0071] Examples 6-7 and Comparative Example 3
[0072] A method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure, compared with Example 1, is different in that, in step S3, the number of PVA-co-PE / AgNW / GO aerogel sheets bonded together is different, and the mass ratio of PVA-co-PE nanofibers, graphene oxide and silver nanowires in each layer is different. The rest is substantially the same as Example 1 and will not be repeated here.
[0073] Example 6 has 5 layers, and the pore sizes of each layer are 5 μm, 20 μm, 40 μm, 60 μm, and 80 μm, respectively; the mass ratios of PVA-co-PE nanofibers, graphene oxide, and silver nanowires in each layer are 9:0.5:0.5, 8:1:1, 6:2:2, 4:3:3, and 2:4:4, respectively.
[0074] Example 7 has 8 layers, and the pore size of each layer is 5 μm, 15 μm, 30 μm, 45 μm, 60 μm, 75 μm, 90 μm, and 100 μm, respectively; the mass ratios of PVA-co-PE nanofibers, graphene oxide, and silver nanowires in each layer are 9:0.5:0.5, 8:1:1, 7:1.5:1.5, 6:2:2, 5:2.5:2.5, 4:3:3, 3:3.5:3.5, and 2:4:4, respectively.
[0075] Comparative Example 3 has 10 layers, and the pore sizes of each layer are 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, and 90 μm, respectively; the mass ratios of PVA-co-PE nanofibers, graphene oxide, and silver nanowires in each layer are 10:0:0, 9:0.5:0.5, 8:1:1, 7:1.5:1.5, 6:2:2, 5:2.5:2.5, 4:3:3, 3:3.5:3.5, 2:4:4, and 1:4.5:4.5, respectively.
[0076] The performance of the high electromagnetic shielding nanofiber aerogels with gradient structures prepared in Examples 6-7 and Comparative Example 3 was tested, and the results are shown in Table 4:
[0077] Table 4 Performance of high electromagnetic shielding nanofiber aerogels prepared in Examples 6-7 and Comparative Example 3
[0078]
[0079] It can be seen from Table 4 that as the number of composite aerogel sheets increases, the overall content of the absorbing medium increases accordingly, and therefore, the electromagnetic shielding performance is enhanced. However, the more layers there are, the thicker the high electromagnetic shielding nanofiber aerogel becomes, which is not conducive to its application. At the same time, the more layers there are, the greater the possibility of debonding between different layers.
[0080] Comparative Example 4
[0081] A method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure. Compared with Example 1, the difference is that the aerogel sheet does not contain PVA-co-PE nanofibers, and is directly prepared from graphene oxide and silver nanowires, and the mass ratio of graphene oxide to silver nanowires is 1:1. The rest is roughly the same as Example 1 and will not be repeated here.
[0082] The conductivity of the high electromagnetic shielding nanofiber aerogel with a gradient structure prepared in Comparative Example 4 is 5000s / cm, the electromagnetic shielding effectiveness is 48.4dB, the absorption frequency band is 9-12.5GHz, and the compressive stress is 139kPa. The performance is reduced, which further shows that the silver nanowires, graphene oxide and PVA-co-PE nanofibers form a special bonded and interwoven structure, which makes the performance better.
[0083] Comparative Example 5
[0084] A method for preparing high electromagnetic shielding nanofiber aerogel, compared with Example 1, the difference is that the pore size of different layers of PVA-co-PE / AgNW / GO aerogel sheets is the same, and the pore size of each layer is 30 μm, only the proportion of raw materials in each layer is different (the proportion of raw materials in each layer is the same as in Example 1), and the rest is roughly the same as Example 1, which will not be repeated here.
[0085] The conductivity of the high electromagnetic shielding nanofiber aerogel prepared in Comparative Example 5 is 5500s / cm, the electromagnetic shielding effectiveness is 53.7dB, the wave absorption frequency band is 8.5-12.5GHz, and the compressive stress is 389kPa, indicating that the performance of the high electromagnetic shielding nanofiber aerogel prepared in the present invention is achieved by the combined effect of the gradient porous structure and the raw material selection.
[0086] Comparative Example 6
[0087] A method for preparing high electromagnetic shielding nanofiber aerogel, compared with Example 1, the difference is that the raw material ratios of different layers of PVA-co-PE / AgNW / GO aerogel sheets are the same, and the ratio of each layer is 4:3:3. The rest is roughly the same as Example 1 and will not be repeated here.
[0088] The high electromagnetic shielding nanofiber aerogel prepared in Comparative Example 6 has an electrical conductivity of 5100 s / cm, an electromagnetic shielding effectiveness of 51.6 dB, an absorbing frequency band of 8.5-13 GHz, and a compressive stress of 392 kPa.
[0089] Comparative Example 7
[0090] A method for preparing high electromagnetic shielding nanofiber aerogel, compared with Example 1, the difference is that the high electromagnetic shielding nanofiber aerogel is a single-layer structure, the mass ratio of PVA-co-PE nanofibers, graphene oxide and silver nanowires is 4:3:3, the pore diameter is 30 μm, and the thickness is the same as that of Example 1. Other details are roughly the same as Example 1 and will not be repeated here.
[0091] The conductivity of the high electromagnetic shielding nanofiber aerogel prepared in Comparative Example 7 is 5200 s / cm, the electromagnetic shielding effectiveness is 44.7 dB, the wave absorption frequency band is 9-12 GHz, the compressive stress is 357 kPa, and the performance is significantly reduced.
[0092] Comparative Example 8
[0093] A method for preparing high electromagnetic shielding nanofiber aerogel, compared with Example 1, the difference is that different layers are randomly bonded, and the pore size of the obtained high electromagnetic shielding nanofiber aerogel is not arranged in order from small to large. The rest is roughly the same as Example 1 and will not be repeated here.
[0094] The high electromagnetic shielding nanofiber aerogel prepared in Comparative Example 8 has an electrical conductivity of 5750 s / cm, an electromagnetic shielding effectiveness of 56.5 dB, an absorbing frequency band of 8-13 GHz, and a compressive stress of 360 kPa.
[0095] In summary, the high electromagnetic shielding nanofiber aerogel with a gradient structure provided by the present invention and the preparation method thereof, PVA-co-PE nanofiber is used as a substrate, graphene oxide and silver nanowires are used as absorbing media, a PVA-co-PE nanofiber suspension is first prepared, and then graphene oxide and silver nanowires are added thereto, and the silver nanowires, graphene oxide and PVA-co-PE nanofibers are bonded and interwoven to form a special bonded interwoven structure; then, through freeze-drying treatment, as water and isopropanol are continuously evaporated, PVA-co-PE / AgNW / GO aerogels with different pore sizes and uniform pores are formed. thin sheet, and finally, the PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are bonded in order from small to large to obtain a high electromagnetic shielding nanofiber aerogel with a gradient structure; utilizing the synergistic effect of silver nanowires, graphene oxide and PVA-co-PE nanofibers as well as the synergistic effect between different layers, when the magnetic waves pass through the high electromagnetic shielding nanofiber aerogel, the electromagnetic waves are continuously reflected and absorbed in the pores of the high electromagnetic shielding nanofiber aerogel with a gradient structure, resulting in excellent electromagnetic shielding performance; solving the problem of narrow absorption frequency of electromagnetic shielding materials and the bottleneck problem of poor electromagnetic shielding performance of conventional materials.
[0096] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure, characterized in that: The steps include: S1. Mix isopropanol, deionized water and PVA-co-PE nanofibers in a certain proportion to prepare a PVA-co-PE nanofiber suspension of a preset concentration; the concentration of the obtained PVA-co-PE nanofiber suspension is 1-5wt%; S2. Adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and freeze-drying to prepare PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes; the mass ratio of the PVA-co-PE nanofibers, graphene oxide and silver nanowires is 9.5:0.25: 0.25-1:4.5:4.5; S3. Several PVA-co-PE / AgNW / GO aerogel sheets prepared in step S2 are bonded in order from small to large pore sizes to obtain a highly electromagnetic shielding nanofiber aerogel with a gradient structure.
2. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: In step S1, the mass ratio of isopropanol, deionized water and PVA-co-PE nanofibers is 49.5:49.5:1-47.5:47.5:
5.
3. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: The diameter of the PVA-co-PE nanofiber is 100-300nm.
4. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: The pore size of the high electromagnetic shielding nanofiber aerogel with a gradient structure is 1-100 μm, and the pore size difference between adjacent PVA-co-PE / AgNW / GO aerogel sheets is 10-90 μm.
5. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: The high electromagnetic shielding nanofiber aerogel with a gradient structure is composed of at least two layers of PVA-co-PE / AgNW / GO aerogel sheets, and the total thickness is no more than 9 mm.
6. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: In step S2, freeze drying is specifically as follows: adding a preset ratio of graphene oxide and silver nanowires to the PVA-co-PE nanofiber suspension prepared in step S1, and adding the suspension to a culture dish, freezing it at (-70)-(-90)°C for 20-30h, and then drying it at (-40)-(-70)°C for 10-80h; the freeze drying treatment of PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes is different.
7. The method for preparing the high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 1, characterized in that: In step S3, PVA-co-PE / AgNW / GO aerogel sheets with different pore sizes are molded and bonded using polydimethylsiloxane.
8. A high electromagnetic shielding nanofiber aerogel with a gradient structure, characterized in that: The aerogel is prepared by the method for preparing a high electromagnetic shielding nanofiber aerogel with a gradient structure as described in any one of claims 1 to 7.
9. The high electromagnetic shielding nanofiber aerogel with a gradient structure according to claim 8, characterized in that: The high electromagnetic shielding nanofiber aerogel has an electrical conductivity of up to 5800s / cm, an electromagnetic shielding effectiveness of up to 56.8dB, and an absorption frequency band of 8-13GHz.
Citation Information
Patent Citations
Elastic controllable graphene aerogel for electromagnetic shielding and preparation method thereof
CN109592964A
Magnetic graphene-based aerogel material with ordered structure and preparation method thereof
CN109320286A
Nano fiber based biomimetic driving film as well as preparation method and application thereof
CN109320742A
Graphene-based aerogel material with strong and tough structure and preparation method thereof
CN109331751A
Preparation method of ternary elastic hydrogel assembled by graphene oxide and silver nanowires
CN109847661A
